Investigating Population Risk Factors of Pancreatic Cancer by Evaluation of Optical Markers in the Duodenal Mucosa - Turzhitsky, Vladimir (IOS Press, 2008)
Pancreatic cancer screening has been hampered by the high rate of complications associated with interrogating the pancreas. The closest non-invasively accessible mucosa available for pancreatic cancer screening is the periampullary duodenal tissue. Our earlier report has shown the potential of using optical markers to interrogate this tissue for the presence of pancreatic cancer. In this study, we report a larger data set of low-coherence enhanced backscattering (LEBS) and elastic light scattering fingerprinting (ELF) optical markers from the periampullary duodenal mucosa. Optical measurements from biopsy samples were acquired from a total of 203 patients with varying clinical classification including healthy controls, a family history of pancreatic cancer, pancreatitis, mucinous cystic precursor lesions, pancreatic cancer, and other pancreatic malignancies. Evaluation of the performance of an independent testing set for discriminating healthy control patients from pancreatic cancer patients showed a 95% sensitivity, 71% specificity, and 85% area under the receiver operator characteristic (AUROC) curve. Importantly, this performance was uncompromised for detecting potentially curable stages of the disease. Additionally, optical markers in higher risk populations such as family history and pancreatitis had values between those of healthy control and pancreatic cancer patients, thus allowing for future investigations of screening from these high risk groups.